A Review of Gassy Sediments: Mechanical Property, Disaster Simulation and In-Situ Test - Liu, Tao; Yang, Xiaotong; Zhang, Yan (Frontiers in Earth Science, 2022)
Gassy sediments are an important cause of engineering disasters such as large-area coastal submarine landslides, excessive tilting of marine foundations, and excessive deformation of tunnels. Under different stress paths, the gassy soil exhibits different microstructure changes and mechanical responses. This paper introduces the current research status regarding the mechanical responses, numerical simulation and the in-situ test methods of gassy sediment. In terms of mechanical responses, it summarized the strength and deformation characteristics of gassy soil under different stress paths, tracking the study on constitutive model. The disaster simulation work using constitutive model of gassy sediment is introduced. It also analyzes the advantages and limitations of various methods in the in-situ test. It can provide theoretical support for further study on disaster prevention and geological risk assessment of gassy sediments.